CHARACTERISTICS OF THE NURSING PROCESS IN CHILD CARE: Akhmedov Ilkhom Ibrokhimovich, Narzullayeva Mehriniso Zayniddinovna, Sitora Sadullaeva Jamolovna - Doctoral student of Bukhara State Medical Institute, Akhmedov Ilkhom Ibrokhimovich; Afshona is a teacher of vocational science at Technical College of Public Health named after Abu Ali Ibn Sina, Narzullayeva Mehriniso Zayniddinovna; Afshona is a vocational science teacher at the technical school of public health named after Abu Ali Ibn Sina, Sitora Sadullaeva Jamolovna (Лучшие интеллектуальные исследования, 2024)
This article discusses the nursing process in pediatrics, focusing on the methods of providing nursing care to healthy and sick children, as well as the interactions between the nurse, the sick child, and the child's parents.